A robust QSCTA-EDRA routing protocol for cognitive radio sensor networks. (8th May 2020) - Bolla, Dileep Reddy; Shankar, Shiva
The exponential rise in wireless communication demands have alarmed academia-industries to develop certain robust routing protocol to achieve quality-of-service (QoS) communication over constrained network conditions. Amongst major wireless communication technologies wireless sensor network (WSN) has been found as the dominant paradigm to meet major communication demands such as surveillance systems, healthcare sector, intelligent transport system, industrial monitoring and control, defence systems, etc. Being a constrained networking technologies WSN demands certain resource efficient (i.e., energy-efficient as well as spectrum efficient) routing protocol to meet exponential up surging demands. Unlike major classical routing protocols, in this paper the prime focus is made on augmenting major functional paradigms of the clustered-CRSN systems by augmenting joint power and resource access/scheduling in intra-cluster as well as inter-cluster data communication, QoS-sensitive cognitive terminal activation (QS-CTA) etc. to achieve energy-efficient dynamic resource access (EDRA) or provision. We have proposed QSCTA-EDRA routing protocol that exploited efficacy of joint-power and resource scheduling and data channel quality (DCQ) and reporting channel quality (RCQ) assisted cognitive terminal activation to accomplish energy-efficient and QoS centric communication over CRSN. Performance comparison for the proposed QSCTA-EDRA routing protocol exhibited that it outperforms existing state-of-art dynamic resource access protocols.